The Continuous Intention of Electricity Mobile Apps: Evidence from Indonesia - Ade Oktarizal Putra; Ratni Prima Lita; Eri Besra; M. Fajar Syafrida (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2025)
Purpose – The low number of active users of the Indonesian state-owned enterprises related to electricity compared to the total number of registered users indicates challenges in promoting sustainable use. This study analyzes the factors influencing continuous intention and use behavior by adopting the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model, which has been expanded to include the variable of trust.Methodology – A quantitative approach, incorporating hypothesis testing techniques, was employed in this study. There were 370 samples, selected using purposive sampling, consisting of PLN Mobile users in West Sumatra who had used the PLN Mobile app within the past three months. Data was collected through an online questionnaire and analyzed using SmartPLS 4.0 software with structural equation modeling techniques.Findings – Hedonic motivation, price value, habit, trust, social influence, performance expectancy, effort expectancy, and facilitating factors all had a positive and significant impact on continuous intention. Habit and facilitating conditions also have a favorable and substantial impact on use behavior. Continuous intention mediates the relationship between trust and use behavior, having a favorable and significant effect on use behavior.Originality/Novelty – This study highlights the role of the UTAUT2 model and trust in influencing sustained intention and usage behavior among mobile application users at state-owned enterprises related to electricity.Implications – The findings of this study will help PLN, as an Indonesian state-owned enterprise related to electricity, understand the significant role of aspects in the UTAUT2 model and trust in shaping sustainable intention and usage behavior among PLN Mobile app users.